Terminological toolkit for studying the concepts of «innovation» and «innovative activity - Kulichenko, Alla; Куліченко, Алла Костянтинівна (Дрогобич: Гельветика, 2020)
The article provides an overview of the interpretation of the terms “innovation” and “innovative activity” in the works of foreign scientists. There is a wide range of definitions of the concept of “innovation” in foreign scientific discourse. The author pays attention to the concepts of “creativity”, “novelty”, “implementation” and “entrepreneurship” to understand the essence of the concept of “innovation”. The article reveals that the term “innovative creativity” means the production of something useful and new by a group of people working together in a complex social system. It also presents that higher education establishments can be the main centers of innovations and innovation activities. If in higher education establishments creativity of the individual is stimulated in the process of interaction, new products and processes can be created, a creative product or process can be implemented, then such institutions are innovative ones. However, the innovative activities of higher education establishments, which can benefit society, are not considered exclusively within the financial aspect. Besides, innovation is a product to be implemented, which includes diversity, intrinsic motivation, and autonomy. It is worth noting that there are many classifications of innovations in the foreign scientific and pedagogical literature, which are presented in the study. The author points out that innovations can be in the form of developing new products; the use of new production methods; the opening of new trading places; creation of new forms of organizations; discovery of new sources of raw materials (according to J. Schumpeter); presented in the form of five generations (according to L. Cagnazzo, et al.), etc. In addition, in the works of foreign researchers innovative activity is interpreted according to the definition of research and development (R & D). The article states that each establishment must have its own definition of innovation, which corresponds to its mission and vision. Moreover, it emphasizes that it is necessary to take into account many aspects when formulating a definition. As for prospects of further researches, they deal with the coverage of innovative activities of higher medical education establishments in Ukraine and the USA in the XXI century. У статті представлено огляд тлумачення термінів «інновація» й «інноваційна діяльність» у працях закордонних учених. Встановлено, що в закордонному науковому дискурсі існує широке коло дефініцій поняття «інновація». Для усвідомлення сутності поняття «інновація» звернуто увагу на концепти «креативність», «новизна», «імплементація» та «підприємництво». Розглянуто термін «інноваційна креативність», що вказує на продукування чогось корисного й нового групою людей, які співпрацюють у складній соціальній системі. Встановлено, що головним осередком інновацій та інноваційної діяльності є заклади вищої освіти. Якщо в закладах вищої освіти творчість особистості стимулюється у процесі взаємодії, можуть бути створені нові продукти та процеси, творчий продукт або процес може бути імплементований, то такі інституції є інноваційними. Проте інноваційна діяльність закладів вищої освіти, що може принести користь суспільству, не розглядається суто в межах фінансового аспекту. Крім того, інновації є продуктом, що підлягає імплементації, до чинників якої належать різноманітність, внутрішня мотивація й автономія. Варто зазначити, що в закордонній науково-педагогічній літературі існують класифікації інновацій, які подані в досліджені. З’ясовано, що інновації можуть бути у вигляді виробництва нових продуктів; використання нових методів виробництва; відкриття нових торговельних місць; створення нових форм організацій; відкриття нових джерел сировини (за Дж. Шумпетером); представлені у вигляді п’яти поколінь (за Л. Кагнаццо й іншими) тощо. Зауважено, що перші покоління інновацій (лінійні інноваційні моделі) не лише не зникли, але й значно просунулися вперед. Констатовано, що інноваційна діяльність у працях закордонних дослідників трактується відповідно до визначення research and development (R & D). Зазначено, що кожна інституція повинна мати власне визначення інновацій, що відповідає її місії та баченню. Водночас підкреслено, що необхідно зважати на низку певних аспектів під час формулювання дефініції. Перспективами подальших досліджень уважаємо висвітлення інноваційної діяльності закладів вищої медичної освіти України та Сполучених Штатів Америки у ХХІ столітті.
Термінологічний інструментарій дослідження понять «інновація» та «інноваційна діяльність»
Keywords: innovation; innovative activity; classification of innovations; creativity; novelty; implementation; entrepreneurship; інновація; інноваційна діяльність; класифікація інновацій; креативність; новизна; імплементація; підприємництво